Comparative Study on 233U and Plutonium Utilization in Molten Salt Reactor - Abdul Waris; Indarta Kuncoro Aji; Yanti Yulianti; Muhamad Ali Shafii; Imam Taufiq; Zaki Su'ud (Indonesian Journal of Physics, 2010)
A comparative study on 233U and Pu utilization in a molten salt reactor (MSR) FUJI-12 has been conducted. Originally, FUJI-12 uses LiF , BeF2 , ThF4 and 233UF4 as fuel. In this study, we have evaluated the use of reactor grade plutonium and weapon grade plutonium beside 233U as the fuel of reactor. The need of 233U concentration for criticality is about 0.34%. In contrast, the demand of the reactor grade plutonium and the weapon grade plutonium fractions for criticality is around 3.0% and 0.96%, correspondingly. The neutron flux in the thermal energy region for 233U fuel case is higher than in Pu fuel cases due to larger value of the average number of neutrons produced per neutron absorbed in 233U fuel than that of 239Pu fuel, and may also because of the hardening of the neutron spectrum owing to plutonium utilization in thermal reactor.